Peran Pendidikan Inklusif Dalam Pembentukan Karakter Saling Nebghargau Di Sekolah Dasar - Maulana, Muhamad Akbar; Muttaqin, Muhammad Fauzan (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This study aims to describe the role of inclusive education in shaping students’ character of mutual respect at the elementary school level. Inclusive education emphasizes equal learning opportunities for all students regardless of differences in abilities, backgrounds, or special needs. This research is grounded in the importance of fostering respect as a fundamental social character in diverse learning environments. A qualitative descriptive approach was employed in this study. The participants consisted of teachers and students in an inclusive elementary school. Data were collected through observation, interviews, and documentation. The findings indicate that inclusive education plays a significant role in developing students’ attitudes of mutual respect, as reflected in positive social interactions, acceptance of differences, empathy, and cooperative behavior among students. Through inclusive learning practices, students learn to appreciate diversity and build respectful relationships. Therefore, inclusive education contributes effectively to character education, particularly in fostering mutual respect among elementary school students.